2019
DOI: 10.1111/jace.16779
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐deficient method lowers grain‐boundary resistivity of doped ceria

Abstract: Nanoparticles of gadolinium‐doped cerium oxide (GDC) were synthesized using solvent‐deficient method and their sinterability and electrical properties were investigated using the powder and cold sintering process. The GDC powder was uniaxially pressed into cylindrically‐shaped pellets with a mixture of nitric acid and hydrogen peroxide at 200°C to encourage particle arrangement during forming process. These bulk samples were annealed using two different temperature profiles: at 800°C for 5 hours and at 1300°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…CeO 2 was also interesting for doping purposes. Gadolinium-doped cerium oxide (GDC) synthesized using the SD method is investigated for its sinterability and electrical properties using the powder and cold sintering process [29]. The low-temperature processing within the SD method is found not to cause significant phase segregation along grain boundaries.…”
Section: Binary Metal Oxidesmentioning
confidence: 99%
“…CeO 2 was also interesting for doping purposes. Gadolinium-doped cerium oxide (GDC) synthesized using the SD method is investigated for its sinterability and electrical properties using the powder and cold sintering process [29]. The low-temperature processing within the SD method is found not to cause significant phase segregation along grain boundaries.…”
Section: Binary Metal Oxidesmentioning
confidence: 99%
“…22 Zeljkovic et al 23 synthesized CeO 2 nanoparticles using a solvent-deficient method and investigated the reaction mechanism and kinetics. Maruyama et al 24 used the same method to synthesize GDC and observed a reduction in grain-boundary resistivity of doped ceria. On the other hand, several studies have proposed the use of sintering aids such as Li, Co, Bi, Cu, and Fe to achieve high-density GDC materials at low sintering temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…30 This technique involves pressing a mixture of particles and a precursor solution under high pressure and at elevated temperatures to achieve highly dense ceramics. CSP has also been successfully employed to prepare densified gadolinia-doped ceria (GDC) by Murutoglu et al, 31 who were able to obtain gastight GDC electrolytes with theoretical densities of up to 96% after sintering at 1100 • C. However, various solvents used in the cold sintering process such as deionized water (heat-treated at 1400 • C), 32 HNO 3 /H 2 O 2 mixture (the relative density of GDC is ∼90%), 24 and molten hydroxides flux solvents (introduced K + and Na + in GDC) 33 have been unable to produce pure and dense GDC ceramics at lower temperatures. Recently, the concept of reactive cold sintering has been introduced for soda-lime glass and BaTiO 3 , 34,35 which enables simultaneous synthesis and densification, offering a green, efficient, and economical way to fabricate dense ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation